Differential geometry of nonholonomic complexes NGr(1, n, 2n − 4) in n-dimensional affine space - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2023)
In this article the differential geometry of the nonholonomic complex NGr(1, n, 2n − 4) in the n-dimensional affine space is studied. The classification of such complexes and geometric interpretations are given.
Keywords: affine space; complex; nonholonomic complex